(untitled) (Medico Legal Update, 2021)
Objective: This study aimed to analysis the associated of serum vitamin D levels and response therapy in advanced lung adenocarcinoma patient after used TKIs. Methods: This study was an observational analytic study. The subjects where patient with advanced lung adenocarcinoma who received tyrosine kinase inhibitors (TKIs) for 3 months at Dr. Soetomo general hospital Surabaya from July to March 2021 who met the inclusion and exclusion criterias. The independent variable in this study are the serum levels of vitamin D and response therapy objective (RECIST criteria) as the dependent variable. Results: The results of stastitical analysis showed that there was no significant associated of serum vitamin D levels and response therapy (p>0.05). Patient insufficiency with partial response had a greater number than patient sufficiency with partial response. The mean of vitamin D levels in patient with progressive disease was the highest. Conclusion: Although the serum levels of vitamin D in lung cancer was lower but in this study showed that there was no significant associated of serum vitamin D levels and response therapy in patient advanced lung adenocarcinoma with tyrosine kinase inhibitors.